O Nurses' Role in Medication Reconciliation in Chronically Ill Patients in Ambulatory Care: A Scoping Review Protocol - Silva, Cláudia (2025)
Introduction: Medication reconciliation being a process that reduces the risk of medication discrepancies, will enable better management of the chronic condition to improve the patient's quality of life and prevent complications. Objective: To map the existing scientific evidence on the role of nurses in medication reconciliation for chronically ill patients in ambulatory care. This knowledge is essential for a more effective and adequate understanding of this phenomenon and to increase the safety and quality of care provided by nurses using evidence-based practice as a reference. Methods: The methodology chosen was a scoping review as proposed by the Joanna Briggs Institute (JBI) and considering the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA-P). To define the eligibility criteria, it was followed the Population, Concept and Context (PCC) reference framework. Based on that, this review will consider studies that address the role of the nurse in medication reconciliation in the chronically ill in ambulatory care. Study selection, data extraction and synthesis will be carried out by two independent reviewers. The review will consider all studies, published and gray literature, without temporal limitations, in any language. Results: The results will be presented in a descriptive way, using tables, considering the objective and focus of the scoping review. Conclusion: It is expected that the results obtained will provide an overview of the importance of the nurse's role in medication reconciliation in chronically ill patients in ambulatory care.